Rancang Bangun Monitoring dan Kendali Akuaponik Berbasis Node-Red - M. Daffarialto Zahrandika Wijaya; Mahendra Widyartono (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2025)
Rapid development and population growth in urban areas have caused various problems, one of which is the decreasing availability of clean water. This has an impact on the agricultural and fisheries sectors which are highly dependent on good water quality. As an alternative to overcome this problem, the aquaponic system offers a solution by combining fish and plant cultivation in one efficient water recirculation system. However, the quality and productivity of the aquaponic system are highly dependent on good management, which requires proper monitoring and control of environmental conditions such as temperature, pH, humidity, and water quality. This study aims to design and build a Node-RED-based aquaponic monitoring and control system. This system uses various sensors to monitor environmental conditions and provide automatic control of parameters that affect plant and fish growth. By using Node-RED as a platform for sensor and control integration, this system is expected to provide an efficient and affordable solution to increase the productivity of the aquaponic system. The results of the study show that the designed tool can carry out effective monitoring and control of parameters that affect the aquaponic system, and can be accessed in real-time to facilitate system management and supervision.